The Implementation of Talking Stick Method to Increase Muslim Prayer Movement Skills as an Extracurricular Program - Yolanda Lusiana Pratama; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the use of the monotonous method of implementing the forum annisa extracurricular activities, namely the lecture method so that the skills of the participants are low. One of the skill tests conducted by the forum annisa is prayer movement skills. Therefore, it is necessary to renew the implementation method, namely applying the talking stick method in the process of implementing the forum annisa activities, especially the prayer movement material. This study aim to see the effect of the application of the talking stick method on improving prayer movemen skills in the extracurricular activities of the  forum annisa for seventh grade students. This type of research is quantitative with an experimental approach with the type of Pre experimental design a one group pretest posttest design. The population of this study were all participants of the VII class forum annisa. Sampling was done by using cluster random sampling technique. Data collection techniques using pretest and posttest. Data collection tools in the form of knowledge tests in the form of question and skills tests in the form of performance appraisal sheets. While the data analysis technique uses the t-test sample correlation formula. The result was a significant effect between the application of the talking stick method on improving prayer movement skills with a value of th < -11.5099 < 2.06 on the knowledge test and th < to -12.0175 < 2.06 on the skills test.